CHARACTERIZATION OF NOVEL ALKALINE PROTEASE PRODUCING STREPTOMYCES FROM ALKALINE SOIL OF LUCKNOW, (U.P.), INDIA. - JYOTI VERMA,; SHIKHA,; DINESH RAJ MODI,; SANGEETA SAXENA, (International Journal of Pharma and Bio Sciences, 2013)
Three alkaline protease producing gram positive, spore forming Streptomyces (J1, J2 and J3) were isolated from alkaline soil (pH range: 9-10) samples collected from Central Soil Salinity Research Institute (C.S.S.R.I), Lucknow. On the basis of halo zone, morphology, texture and microscopic characteristics they were identified as Streptomyces. Further characterization both genetically and phenotyphically were done in order to establish their phylogeny. The results of the 16S rDNA sequences were analysed using BLASTn. On the basis of the homology results the isolates ((J1, J2 and J3) were identified as S. macrosporeus, S. bacillaris, and S. rubrolavendulae, respectively. Optimization studies under different carbon and nitrogen sources at pH 10 under 72 h of incubation revealed maximum protease production by S. rubrolavendulae (12.50 U/ml) and S. bacillaris (8.82U/ml) and the minimum by S. macrosporeus (0.95 U/ml). The crude alkaline protease thus revealed maximum activity at 37 0C at pH 10.